Adubação nitrogenada em pastagem de papuã (Urochloa plantaginea (Link) Hitch) - Salvador, Paulo Roberto (2018)
Knowledge of the productive potential of the species, in response to nitrogen (N) fertilization, can reduce the risk of environmental contamination, since to minimize losses of N, this nutrient must be supplied in an amount equal to or less than the maximum capacity of absorption by plants. Studies that aim to determine N levels that do not exceed the grasses' response capacity are among the biggest challenges of production systems, which are to reduce environmental impact, produce quality food, reduce production costs and increase efficiency of N. The Alexandergrass (Urochloa plantaginea (Link) Hitch) has been studied and presents desirable characteristics as a forage species. The objective of this study was to study the efficiency of N use in Alexandergrass by means of information on pasture characteristics, nitrogen nutrition index, morphogenesis, biomass flows, utilization efficiency and leaf blades net balance. The experiment was carried out in the area of the Department of Animal Science of the UFSM, with field evaluations from January to March 2014. The treatments were composed of Alexandergrass pasture, fertilized with zero, 150 or 300 kg of N/hectare (ha). The experimental area (4.8 ha) was divided into six experimental units (paddock) of 0.8 ha, subdivided into four plots. Angus heifers were used, with initial mean age of 15 months. The grazing method was a rotational stocking grazing and the animals were managed to keep 30±5 cm in the post grazing sward height. The experimental design was the completely randomized, with measures repeated in the time, with three treatments and two area repetitions. Nitrogen nutrition index increased linearly as a function of N levels (Ŷ=59.8+0.1216N). The leaf appearance rate was adjusted to the positive linear regression model as a function of the thermal sum with zero of N (Ŷ0N=0.0077+0.0000087ST) and 150 kg/ha of N (Ŷ150N=0.0020+0,000021ST). With the use of 300 kg/ha of N the leaf appearance rate was not altered (0.0124 leaf/degree-day). The senescence flow in the basal tiller reduced linearly as a function of N levels (Ŷ=34.6-0.036N). The leaf blades flow of the axillary tillers, when applied 150 kg/ha of N, was adjusted to the positive linear regression model as a function of ST. The use of up to 300 kg/ha of N increases the nitrogen content of the Alexandergrass. The leaf appearance rate in Alexandergrass is dependent on the use of N, and the other morphogenic and structural characteristics of the tiller are not altered. The tillering dynamics of the Alexandergrass is modified by the use of N fertilization at levels higher than 150 kg/ha. The use of N, regardless of the level, increases the flow of stem growth and decreases the leaf senescence flow in the basal tiller. In axillary tillers, N positively influences the growth flow and provides less liquid balance of leaf blades. The use of N in Alexandergrass does not modify the efficiency of use of the leaf blades of the basal and axillary tiller.